2020
DOI: 10.1111/tpj.15079
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of EARLY LESION LEAF 1, encoding a cytochrome P450 monooxygenase, induces ROS accumulation and cell death in rice

Abstract: Lesion-mimic mutants (LMMs) provide a valuable tool to reveal the molecular mechanisms determining programmed cell death (PCD) in plants. Despite intensive research, the mechanisms behind PCD and the formation of lesions in various LMMs still remain to be elucidated. Here, we identified a rice (Oryza sativa) LMM, early lesion leaf 1 (ell1), cloned the causal gene by map-based cloning, and verified this by complementation. ELL1 encodes a cytochrome P450 monooxygenase, and the ELL1 protein was located in the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 66 publications
5
61
0
Order By: Relevance
“…In the present study, Pro accumulated in the OsAAP3 OE lines, but decreased in the Ri lines ( Figure S3 ), indicating that Pro may be involved in the ROS pathway. As the MDA content indirectly reflects the degree of cellular damage [ 26 ], our results also showed that the MDA content in the OsAAP3 OE lines was significantly increased ( Figure 2 D), as observed for the ell1 mutant with ROS accumulation and lesion formation [ 27 ].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In the present study, Pro accumulated in the OsAAP3 OE lines, but decreased in the Ri lines ( Figure S3 ), indicating that Pro may be involved in the ROS pathway. As the MDA content indirectly reflects the degree of cellular damage [ 26 ], our results also showed that the MDA content in the OsAAP3 OE lines was significantly increased ( Figure 2 D), as observed for the ell1 mutant with ROS accumulation and lesion formation [ 27 ].…”
Section: Discussionsupporting
confidence: 68%
“…The staining results indicated that the OsAAP3 OE lines might give rise to the production of cell death in rice leaf. In recent years, there are many reports about the mechanism of ROS mediated cell death [ 2 , 27 , 33 ]. For example, the mutation in ELL1 disrupted the structure of chloroplast, then further caused accumulation of ROS, which ultimately triggered cell death of rice leaf [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the single base substitution in the LOC_Os12g16720 locus confers the mosaic spot lesion phenotype of both mutants msl-1 and msl-2. This conclusion has been supported by the recently published research on ell1 (early lesion leaf 1) and sl-MH-1, which are LMM mutants from the japonica rice variety Wuyunjing7 and indica rice line Minghui 86 (MH86), respectively, at the LOC_Os12g16720 locus (Tian et al, 2020;Cui et al, 2021).…”
Section: Fine Mapping Of Msl-1 and Msl-2mentioning
confidence: 64%
“…It has been shown that serotonin is involved in the immune response of plants, and exogenous applied serotonin enhances resistance to Magnaporthe grisea (M. grisea) in the sl mutant (Fujiwara et al, 2010). In addition, the serotonin is acknowledged to be a kind of strong antioxidant compounds by scavenging ROS (Huether et al, 1997), which is in agreement with excessive ROS accumulation in the sl mutants (Cui et al, 2021; Figure 3). Excessive ROS accumulation triggers off programmed cell death (PCD)-mediated cell apoptosis, causing the lesion formation in rice (Cui et al, 2021).…”
Section: The Mutation Of Cyp71p1 Leads To Premature Senescencementioning
confidence: 64%
See 1 more Smart Citation